Collective Efficacy in Sports and Physical Activities: Perceived Emotional Synchrony and Shared Flow - Zumeta, Larraitz N.; Oriol, Xavier; Telletxea, Saioa; Amutio, Alberto; Basabe, Nekane (Frontiers in Psychology, 2016)
This cross-sectional study analyzes the relationship between collective efficacy and two psychosocial processes involved in collective sport-physical activities. It argues that in-group identification and fusion with the group will affect collective efficacy (CE). A sample of 276 university students answered different scales regarding their participation in collective physical and sport activities. Multiple-mediation analyses showed that shared flow and perceived emotional synchrony mediate the relationship between in-group identification and CE, whereas the relationship between identity fusion and CE was only mediated by perceived emotional synchrony. Results suggest that both psychosocial processes explain the positive effects of in-group identification and identity fusion with the group in collective efficacy. Especially, the role of perceived emotional synchrony in explaining the positive effects of participation in collective sport-physical activities is underlined. In sum, this study remarks the utility of collective actions and social identities to explain the psychosocial processes related to collective efficacy in physical and sports activities. Finally, practical implications are discussed.